Rev Cuid 2021
DOI: 10.15649/cuidarte.2044
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos, actitudes, prácticas, temor y estrés ante el Covid-19 en estudiantes y recién egresados de Enfermería en Colombia

Abstract: Introducción: La pandemia por Covid-19 ha tenido una afectación de la salud emocional del recurso humano en salud, a pesar de contar con conocimientos sobre el virus y su manejo, el personal sanitario entre el que está Enfermería, presenta estrés y temor ante el Covid-19.  Objetivo. Describir y correlacionar el nivel de temor, estrés, conocimientos, actitudes y prácticas frente al Covid-19 en estudiantes y recién egresados de Enfermería en Colombia. Método. Se realizó un estudio observacional de carácter trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…17 Studies in Europe, North America and some in Latin America reported similar needs and raised conditions that require valid mechanisms to approximate a reliable measure in processes of estimating the occurrence of problems associated with the presence of infectious diseases, considering the high emotional burden and the need to promote decision-making based on evidence related to the experience of providing health services, including academic practice settings. 21,[29][30][31][32][33][34] The results of the present study should be analyzed with caution, considering the sampling method, a condition that limits the ability to generalize the findings. Additionally, it is necessary to consider that the analysis plan did not consider criteria of temporal stability and invariance of the factors based on criteria such as gender, age or academic program, conditions that would increase the scope of establishing the psychometric properties of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…17 Studies in Europe, North America and some in Latin America reported similar needs and raised conditions that require valid mechanisms to approximate a reliable measure in processes of estimating the occurrence of problems associated with the presence of infectious diseases, considering the high emotional burden and the need to promote decision-making based on evidence related to the experience of providing health services, including academic practice settings. 21,[29][30][31][32][33][34] The results of the present study should be analyzed with caution, considering the sampling method, a condition that limits the ability to generalize the findings. Additionally, it is necessary to consider that the analysis plan did not consider criteria of temporal stability and invariance of the factors based on criteria such as gender, age or academic program, conditions that would increase the scope of establishing the psychometric properties of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this study's findings highlight the importance of not only increasing knowledge but also translating that knowledge into practical, preventive behaviors. Tailored health education strategies, coupled with efforts to enhance confidence in government measures, can play a crucial role in promoting better compliance with recommended practices and reducing the risk of COVID-19 infection [37].…”
Section: Discussionmentioning
confidence: 99%
“…La pandemia reveló un sistema de salud débil, precaria infraestructura, y deficiente logística, así como poca o nula investigación, población geriátrica abandonada, profesionales mal remunerados, falta de seguro de salud y el despliegue completo y retrasado de protecciones de fondos, lo que aumentó el riesgo de impactos en la salud mental de muchos (Gobierno del Perú, 2023;Osorio-Martínez et al, 2022). Este acontecimiento, como resultado de algunas medidas para hacerle frente como el aislamiento social y otras situaciones asociadas a ella, y los denodados esfuerzos que hicieron algunos profesionales para la contención de la enfermedad, representaron un gran reto para la salud mental, pues según estimaciones e investigaciones mostraron un número significativo de secuelas psicosociales tanto a nivel personal como a nivel comunitario, estos múltiples problemas de índole psicológico aparecieron desde síntomas aislados como la frustración, estrés, el miedo, la impotencia, la rabia y la ansiedad hasta problemas psicopatológicos, debido a que las personas se enfrentaron a un escenario desconocido (Carreño-Moreno et al, 2021;Ramírez-Ortiz et al, 2020).…”
Section: Introductionunclassified